A WAVELET ANALYSIS OF BOLD SIGNALS OBTAINED IN MR STUDIES FOR ADHD DIAGNOSIS - Dulce Isabel Gonzalez-Gomez; Javier Miguel Hernandez Lopez; Eduardo Moreno Barbosa; Mario Ivan Martınez Hernandez; Silvia Hidalgo Tobon; Benito de Celis Alonso (European Scientific Journal, ESJ, 2014)
A series of wavelet analysis techniques were applied to the Blood Oxygen Level Dependent (BOLD) signals of Functional Magnetic Resonance Images (fMRI) of healthy children and a group diagnosed with Attention deficit hyperactivity disorder (ADHD). Imaging was performed on a total of 15 subjects (ages between 4 – 13 years) divided into Healthy (H) and ADHD (AD) groups. The 1.5T Philips scanner from ``Hospital Infantil de México Federico Gómez´´ was used to obtain data. Statistically significant differences were found for the wavelet scale and the frequency parameters between the H and the AD groups. These results point towards the future use of these techniques as diagnostic tools.